Thermal Engineering of Conventional Heating Devices for Manual Tire Patching: Energy, Heat, and Operational Safety Study - Rizki Ilmianih; Arief Muliawan (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2025)
This research examines the design and thermal analysis of a gasoline-based heating device that functions as a heating medium in the manual tire patching process. The working principle of this device is to generate heat through gasoline combustion to optimally bond the patch material with the tire surface. This study aims to assess the heat efficiency, energy consumption, and safety and environmental sustainability aspects of the heating system. Data collection was conducted through direct observation of tire patch workshop businesses in the local community. Based on the test results, the tool is able to reach working temperatures between 244°C and 289°C, with a relatively short heating time of about 2 to 3 minutes per cycle. In addition to providing time efficiency, it is also energy-efficient, requiring only about 1 liter of gasoline for multiple uses. Performance tests show that it produces low emissions, making it more environmentally friendly than the conventional methods commonly used. With affordable production costs and simple construction, this tool can be an effective and applicable alternative solution for small businesses in the field of tire patching services.